Phase II study of atezolizumab with bevacizumab for non-squamous non-small cell lung cancer with high PD-L1 expression (@Be Study). Issue 2 (1st February 2022) - Seto, Takashi; Nosaki, Kaname; Shimokawa, Mototsugu; Toyozawa, Ryo; Sugawara, Shunichi; Hayashi, Hidetoshi; Murakami, Haruyasu; Kato, Terufumi; Niho, Seiji; Saka, Hideo; Oki, Masahide; Yoshioka, Hiroshige; et al.
Abstract : Background: PD-L1 expression on tumor cells is a marker of PD-1/PD-L1 antibody treatment efficacy for advanced non-small cell lung cancer (NSCLC). PD-L1 antibody (atezolizumab) prolongs overall survival (OS) compared with platinum doublet as first-line treatment for NSCLC with high PD-L1 expression. Bevacizumab enhanced cytotoxic agent and epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor efficacy in non-squamous (NS)-NSCLC, and PD-1/PD-L1 antibodies in preclinical models. Methods: This single-arm phase II study investigated clinical benefits of adding bevacizumab 15 mg/kg to atezolizumab 1200 mg fixed dose in a first-line setting for advanced NS-NSCLC patients with PD-L1 expression ≥50% without EGFR / ALK / ROS1 alterations. Primary endpoint was objective response rate (ORR) assessed by central review committee. Secondary endpoints were progression-free survival (PFS), duration of response (DOR), OS, and safety. Results: Of 39 enrolled patients, 33 (84.6%) had stage IV NSCLC and 36 (92.3%) had smoking history. As of March 31, 2020, no patient had a complete response and 25 patients had a partial response (ORR=64.1%, 95% CI 47.18 to 78.80). Twelve-month PFS and OS rates were 54.9% (35.65 to 70.60) and 70.6% (50.53 to 83.74), respectively. The median DOR in 25 responders was 10.4 months (4.63–not reached). The median treatment cycle was 12 (1 to 27). Nineteen patients discontinued study treatment because of disease progression (N=17) or immune-related adverse events (AEs) (N=2) (sclerosing cholangitis or encephalopathy). There were 23 serious AEs in 12 patients, but no grade 4/5 toxicity. Conclusions: Atezolizumab with bevacizumab is a potential treatment for NS-NSCLC with high PD-L1 expression. Trial registration number: JapicCTI-184038.